2020
DOI: 10.7150/ijbs.45120
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Mental Health Services during the COVID-19 Outbreak in China

Abstract: The novel coronavirus disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
874
2
119

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,039 publications
(1,095 citation statements)
references
References 12 publications
17
874
2
119
Order By: Relevance
“…5 The outbreak of communicable diseases is widely perceived as a traumatic event leading to a significant increase in anxiety, depression and fear levels. 6,7 During the outbreak of the Severe Acute Respiratory Syndrome (SARS) 8 and the Middle Eastern Respiratory Syndrome (MERS) 9 , the quarantined individuals had more negative emotions like anxiety and anger which are consistent with the findings from isolated mice experiments. 10 Hu et al found that the type of quarantine can affect the level of anxiety during the COVID-19 outbreak in China.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…5 The outbreak of communicable diseases is widely perceived as a traumatic event leading to a significant increase in anxiety, depression and fear levels. 6,7 During the outbreak of the Severe Acute Respiratory Syndrome (SARS) 8 and the Middle Eastern Respiratory Syndrome (MERS) 9 , the quarantined individuals had more negative emotions like anxiety and anger which are consistent with the findings from isolated mice experiments. 10 Hu et al found that the type of quarantine can affect the level of anxiety during the COVID-19 outbreak in China.…”
supporting
confidence: 71%
“…11 Mass quarantine restrictions on non-emergency health services including psychiatric care may adversely affect the access of vulnerable populations to mental health care which cannot be provided by health professionals in isolation units and hospitals due to a lack of specialized training. 7,12 Posttraumatic stress disorder (PTSD) is a mental health condition characterized by heightened anxiety that can also occur in response to diseases outbreaks. The immediate increase of posttraumatic stress symptoms (PTSS) among patients, healthcare workers, and general population following outbreaks of the SARS, MERS, Ebola, and Zika -had been studied longitudinally in order to evaluate the long-term consequences of these diseases' outbreaks.…”
mentioning
confidence: 99%
“…The suspected and/or confirmed COVID-19 persons largely experience fear regarding the high contagiousness and fatality (Wang et al 2020a;Li et al 2020…”
Section: Among Covid-19 Casesmentioning
confidence: 99%
“…24,25 China has now widely launched online psychological intervention services, including psychological counseling via telephone hotlines and intervention platforms. 26 Considering that the current epidemic of Covid-19 has spread worldwide, the psychological problems of the public might persist or further develop for a long period. It would remain a problem worthy of consideration and attention that how to better allocate limited medical resources to provide psychophysiological support for patients with chronic diseases and rare diseases, such as SAPHO syndrome.…”
Section: ) Discussionmentioning
confidence: 99%